2013
DOI: 10.5935/1808-8694.20130030
|View full text |Cite
|
Sign up to set email alerts
|

Cervicomastoidfacial versus modified rhytidectomy incision for benign parotid tumors

Abstract: Modified rhytidectomy incision has shown comparable complication rates to those of the classic approach and a lower incidence of immediate facial movement impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…Salivary fistula was reported in 137 studies 6–10,12,14–16,18–24,27,28,30–34,36,38–40,43–45,47,49,51,52,55,56,58,62–65,75,76,79,84–87,89,91,93,97–99,101,103–109,112,114–119,124–127,129,131–133,136,138,139,141,144,148–150,153,154,156,164,166,170–215 reporting on 18,815 patients (Table I and Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salivary fistula was reported in 137 studies 6–10,12,14–16,18–24,27,28,30–34,36,38–40,43–45,47,49,51,52,55,56,58,62–65,75,76,79,84–87,89,91,93,97–99,101,103–109,112,114–119,124–127,129,131–133,136,138,139,141,144,148–150,153,154,156,164,166,170–215 reporting on 18,815 patients (Table I and Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled incidence of salivary fistula reported was 3.1% (95% CI: 2.6‐3.7), with a minimum of 0% and a maximum of 21.0%, indicating large heterogeneity among studies ( I 2 = 74.8%). Factors associated with an increased incidence of salivary fistula include implants (fibrin glue, 30 Gore‐Tex, 33 acellular dermal matrix 164,196 ), parotidectomy for sialadenitis, 63,132,186 less extensive parotidectomy, 112,198,200,212 SMAS dissection and lifting incision, with or without a sternocleidomastoid flap 28,99,104,188,202,205 . In several studies, no clear explanation could be found 47,105,182,200,209 …”
Section: Resultsmentioning
confidence: 99%
“…The present study also showed that the parotid tumor size was smaller in the MFI group than in the MBI group. Although different medical facilities may have different protocols for choosing the incision type and comparable tumor sizes between the two incision groups have been reported 18 , 19 , the presented pooled data suggest that physicians seem to consider using the MFI for patients with smaller tumors. One of the included studies suggested that MFI is more suitable for tumors in the lower and posterior portions of the parotid gland 20 , while several authors indicated that MFI can be used in parotidectomy regardless of tumor location 17 , 19 .…”
Section: Discussionmentioning
confidence: 83%
“…The pooled results of five studies 14 , 16 , 18 20 showed no significant difference between the two groups in terms of the rate of salivary complications (RD = − 0.00; 95% CI − 0.05 to 0.05; I 2 = 0.00%) (Fig. 5 B).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation